2011
DOI: 10.1016/j.bandl.2011.04.006
|View full text |Cite
|
Sign up to set email alerts
|

BOLD response to motion verbs in left posterior middle temporal gyrus during story comprehension

Abstract: A primary focus within neuroimaging research on language comprehension is on the distribution of semantic knowledge in the brain. Studies have shown that the left posterior middle temporal gyrus (LPMT), a region just anterior to area MT/V5, is important for the processing of complex action knowledge. It has also been found that motion verbs cause activation in LPMT. In this experiment we investigated whether this effect could be replicated in a setting resembling real life language comprehension, i.e. without … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(35 citation statements)
references
References 49 publications
0
35
0
Order By: Relevance
“…This raises the possibility that verb selectivity in the left LTC may be driven primarily by semantic differences between action verbs and object nouns. Indeed, several studies have found that sentences referring to actions activate regions in LTC (Wallentin et al, 2011;Deen & McCarthy, 2010;Rueschemeyer, Glenberg, Kaschak, Mueller, & Friederici, 2010;Saygin, McCullough, Alac, & Emmorey, 2010;Hauk, Davis, Kherif, & Pulvermuller, 2008;Wallentin, Lund, Ostergaard, Ostergaard, & Roepstorff, 2005;Davis, Meunier, & Marslen-Wilson, 2004), including a verb-selective region in STS (Davis et al, 2004). However, a recent study investigating responses in functionally localized verb-selective LTC regions showed that these regions are not modulated by the amount of visual motion or motor activity associated with verbs, with equally selective responses to verbs such as to jump and to think (Bedny et al, 2008).…”
Section: Introductionmentioning
confidence: 95%
“…This raises the possibility that verb selectivity in the left LTC may be driven primarily by semantic differences between action verbs and object nouns. Indeed, several studies have found that sentences referring to actions activate regions in LTC (Wallentin et al, 2011;Deen & McCarthy, 2010;Rueschemeyer, Glenberg, Kaschak, Mueller, & Friederici, 2010;Saygin, McCullough, Alac, & Emmorey, 2010;Hauk, Davis, Kherif, & Pulvermuller, 2008;Wallentin, Lund, Ostergaard, Ostergaard, & Roepstorff, 2005;Davis, Meunier, & Marslen-Wilson, 2004), including a verb-selective region in STS (Davis et al, 2004). However, a recent study investigating responses in functionally localized verb-selective LTC regions showed that these regions are not modulated by the amount of visual motion or motor activity associated with verbs, with equally selective responses to verbs such as to jump and to think (Bedny et al, 2008).…”
Section: Introductionmentioning
confidence: 95%
“…But they are more frequently regarded as forming a subset of the functional network thought to enable representation of the visual and somatomotor features of actions when they are perceived, performed, conceptualized, and verbally processed (Caspers et al, 2010;Kemmerer et al, 2012;Molenberghs et al, 2012;Pulvermuller, 2013;Watson et al, 2013;Rizzolatti et al, 2014;Urgesi et al, 2014;Kemmerer, 2015). This included a region of the left posterior MTG that has been associated with encoding the visual motion components of action concepts (Chen et al, 2008;Deen and McCarthy, 2010;Saygin et al, 2010;Wallentin et al, 2011;Humphreys et al, 2013;Watson et al, 2013). Interestingly, this seems to contrast with the view that the left posterior MTG represents more schematic aspects of the event structures encoded by both action and non-action verbs/sentences (Bedny et al, 2008(Bedny et al, , 2012.…”
Section: Brain Regions For Conceptualizing An Action At Different Loasmentioning
confidence: 99%
“…Furthermore, when the linguistic context is stronger, that is, when stimuli are sentences or narratives describing motion, studies have found activation of motion processing areas more proximal to MT+ (Wallentin et al, 2011;Saygin, McCullough, Alac, & Emmorey, 2010).…”
mentioning
confidence: 99%